PERAN KEMITRAAN PETANI DENGAN PT.SANG HYANG SERI TERHADAP PENINGKATAN PENDAPATAN - Rasdiana Mudatsir; Asriyanti Syarif; Sumarni B (Fapetrik-UMPAR, 2022)
Sang Hyang Seri collaborates with breeder farmers to produce seeds through a partnership program. Partnership evaluation can be done to see how far the implementation of the partnership between PT. Sang Hyang Seri with partner farmers has been running so that the problems encountered during the implementation of the partnership can be identified. The purpose of this study was to determine the benefits of partnerships between farmers and farmers PT. Sang Hyang Seri, analyze the level of satisfaction of farmers with the partnership program with PT. Sang Hyang Seri, analyze the income level of farmers who are in partnership with PT. Sang Hyang Seri. The results of this study are several of the benefits derived from the farmer partnership with PT. Sang Hyang Seri is through a partnership program, farmers will get assistance with production facilities, market guarantees, the company's purchase price is higher than the prevailing market price, increased farmer skills, better production quality, and increased farmer income. The level of farmer satisfaction with the partnership program with PT. Sang Hyang Seri is with a Customer Satisfaction Index value of 81.12 which is in the range of 0.81-1.00 which indicates that the consumer satisfaction index is on the